Analysis of the current state and diagnosis of key problems of public administration in the healthcare sector in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2024)
Healthcare is one of the most important areas of activity of any state. One of the goals of sustainable development, the United Nations (UN) proclaims "Ensuring a healthy lifestyle and promoting well-being for all at any age." The efforts of all countries of the world are directed towards the realization of this goal, since the health of the nation and the high standard of living of the country's population are important components of the sustainable development of each country.  In this regard, the article emphasizes that healthcare is one of the most important areas of activity of any state, and effective public administration in this area is critical, so the goal was to develop proposals and recommendations to ensure high-quality and affordable medical care for all segments of the population. For this purpose, various research methods were used, such as the method of scientific abstraction, the method of induction and deduction, literature analysis and statistical analysis of modern data in dynamics over the past 5 years, the method of generalization and comparative analysis, which were used to identify problems and develop recommendations to improve the availability and quality of medical care, ensure public health and improve the quality of life of the population. In light of the challenges Kazakhstan has faced in public health management, including pandemics, demographic changes and technological innovations, we have proposed: introducing an automated data processing system in all regions of the country, improving the system of monitoring and analyzing health management, optimizing the financing system, developing a mechanism for monitoring and overseeing the provision of high-quality and affordable medical care to all segments of the population.Key words: health, healthcare, affordable medical care, quality of life, pandemic, recommendations, public health management